Role of the endocannabinoid system in the neuroendocrine responses to inflammation - de Laurentiis, Andrea (2014)
A few years ago the endocannabinoid system has been recognized as a major neuromodulatory system whose main functions are to exert and maintain the body homeostasis. Several different endocannabinoids are synthesized in a broad class of cell types, including those in the brain and the immune system; they bind to cannabinoid G-protein-coupled receptors, having profound effects on a variety of behavioral, neuroendocrine and autonomic functions. The coordinated neural, immune, behavioral and endocrine responses to inflammation are orchestrated to provide an important defense against infections and help homeostasis restoration in the body. These responses are executed and controlled mainly by the hypothalamic-pituitary adrenal axis. Also, the hypothalamic-neurohypophyseal system is essential for survival and plays a role recovering the homeostasis under a variety of stress conditions, including inflammation and infection. Since the endocannabinoid system components are present at sites involved in the hypothalamic-pituitary axis regulation, several studies were performed in order to investigate the endocannabinoid-mediated neurotransmitters and hormones secretion under physiological and pathological conditions. In the present review we focused on the endocannabinoids actions on the neuroendocrine response to inflammation and infection. We provide a detailed overview of the current understanding of the role of the endocannabinoid system in the recovering of homeostasis as well as potential pharmacological therapies based on the manipulation of endocannabinoid system components that could provide novel treatments for a wide range of disorders.